Critical role of c-Jun overexpression in liver metastasis of human breast cancer xenograft model - Qian Lu; Song Yuhua; Chen Liyong; Shi Ming; Pu Xiaoyun; Zhang Yan; Yuan Guogang; Zhang Hao; Yu Ming; Hu Meiru; Shen Beifen; Guo Ning (BMC Cancer, 2007)
Abstract Background c-Jun/AP-1 has been linked to invasive properties of aggressive breast cancer. Recently, it has been reported that overexpression of c-Jun in breast cancer cell line MCF-7 resulted in increased AP-1 activity, motility and invasiveness of the cells in vitro and tumor formation in nude mice. However, the role of c-Jun in metastasis of human breast cancer in vivo is currently unknown. Methods To further investigate the direct involvement of c-Jun in tumorigenesis and metastasis, in the present study, the effects of c-Jun overexpression were studied in both in vitro and in nude mice. Results Ectopic overexpression of c-Jun promoted the growth of MCF-7 cells and resulted in a significant increase in the percentage of cells in S phase and increased motility and invasiveness. Introduction of c-Jun gene alone into weakly invasive MCF-7 cells resulted in the transfected cells capable of metastasizing to the nude mouse liver following tail vein injection. Conclusion The present study confirms that overexpression of c-Jun contributes to a more invasive phenotype in MCF-7 cells. It indicates an interesting relationship between c-Jun expression and increased property of adhesion, migration and in vivo liver metastasis of MCF-7/c-Jun cells. The results provide further evidence that c-Jun is involved in the metastasis of breast cancer. The finding also opens an opportunity for development of anti-c-Jun strategies in breast cancer therapy.